Anomalous water dynamics at surfaces and interfaces: synergistic effects of confinement and surface interactions. (5th December 2017) - Biswas, Rajib; Bagchi, Biman
Abstract: In nature, water is often found in contact with surfaces that are extended on the scale of molecule size but small on a macroscopic scale. Examples include lipid bilayers and reverse micelles as well as biomolecules like proteins, DNA and zeolites, to name a few. While the presence of surfaces and interfaces interrupts the continuous hydrogen bond network of liquid water, confinement on a mesoscopic scale introduces new features. Even when extended on a molecular scale, natural and biological surfaces often have features (like charge, hydrophobicity) that vary on the scale of the molecular diameter of water. As a result, many new and exotic features, which are not seen in the bulk, appear in the dynamics of water close to the surface. These different behaviors bear the signature of both water–surface interactions and of confinement. In other words, the altered properties are the result of the synergistic effects of surface–water interactions and confinement. Ultrafast spectroscopy, theoretical modeling and computer simulations together form powerful synergistic approaches towards an understanding of the properties of confined water in such systems as nanocavities, reverse micelles (RMs), water inside and outside biomolecules like proteins and DNA, and also between two hydrophobic walls. We shall review the experimental results and place them in the context of theory and simulations. For water confined within RMs, we discuss the possible interference effects propagating from opposite surfaces. Similar interference is found to give rise to an effective attractive force between two hydrophobic surfaces immersed and kept fixed at a separation of d, with the force showing an exponential dependence on this distance. For protein and DNA hydration, we shall examine a multitude of timescales that arise from frustration effects due to the inherent heterogeneity of these surfaces. We pay particular attention to the role of orientational correlations and modification of the same due to interaction with the surfaces.